Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd007145.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing excessive weight gain during pregnancy

Abstract: Background Excessive weight gain during pregnancy is associated with multiple maternal and neonatal complications. However, interventions to prevent excessive weight gain during pregnancy have not been adequately evaluated. Objectives To evaluate the effectiveness of interventions for preventing excessive weight gain during pregnancy and associated pregnancy complications. Search methods We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (20 October 2011) and MEDLINE (1966 to 20 Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 80 publications
(233 reference statements)
3
106
0
4
Order By: Relevance
“…Similarly, Choi et al 54 showed that gestational weight gain was lower following a supervised physical activity intervention (WMD=−1.74 kg, 95% CI −3.66 to +0.19, p=0.077), with two studies included in the analyses. In contrast, Muktabhant et al 55 performed a Cochrane Review on interventions for preventing excessive weight gain during pregnancy. These authors concluded that there was not enough evidence to recommend any intervention, including exercise, for preventing excessive gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Choi et al 54 showed that gestational weight gain was lower following a supervised physical activity intervention (WMD=−1.74 kg, 95% CI −3.66 to +0.19, p=0.077), with two studies included in the analyses. In contrast, Muktabhant et al 55 performed a Cochrane Review on interventions for preventing excessive weight gain during pregnancy. These authors concluded that there was not enough evidence to recommend any intervention, including exercise, for preventing excessive gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercaloric nutrition, for instance, as well as a lack of physical activity raises the risk for both increased weight and/or gestational diabetes [38,39]. The associated maternal hyperglycemia leads to continuing fetal hyperglycemia and overstimulation of the perinatal pancreatic B cells as well as to hyperinsulinemia with an increased risk of the development of type 1 diabetes in the fetus [40].…”
Section: Selected Factors Of Molecular Biology and Geneticsmentioning
confidence: 99%
“…Excessive gestational weight gain (GWG) puts both mother and baby at risk for obesity and subsequent obesity related chronic disease [1, 3-6]. Interventions targeting GWG have only been somewhat successful, and more so for select groups[7]. For example, normal weight, higher income women, and those receiving exercise and/or nutritional counseling respond better to the interventions and are less likely to exceed GWG recommendations during pregnancy than overweight, lower income women, and those receiving no advice [8-11].…”
Section: Introductionmentioning
confidence: 99%